Health professional students' preparedness for E-Health - A. Al-Tawaty, Adel; Omar Elfallah, Ehab (Libyan International Medical University Journal, 2019)
Background: E-Health is one of the recent major developments in health-care provision. Today's health professional students are considered digitally oriented, and this may endow them with the necessary capabilities to implement E-Health on graduation. Aim: This study aimed to assess students' views, use, confidence, and need for training on E-Health. Participants: Fourth-, 5th- and internship-year students of the medical and dental schools at the Libyan International Medical University constituted the study population. Methodology: This is a cross-sectional study conducted using an online administered survey. Prior to implementation, the questionnaire was reviewed by experts and then piloted on a group of research-targeted students. Likert scale was used for most questions and few were in the form of short answers. Descriptive statistics were reported using SPSS software version 23.0. Results: One hundred and two students responded, and all responders were included for most select-response questions. The male-to-female ratio was 2:3, with a mean age of 24 ± 1.8 years. Medical students accounted for 52% of the participants. An average of 45% reported proficiency in written and spoken English. Only 12% have taken IT-related courses. Their view on E-Health was moderately positive with a mean of 3.5 ± 0.34 of 3.1 ± 1.029. In spite of this, 43% ± 3.9% had negative views on E-Health. Nearly 58% of the participants used digital tools and software with a mean score of 2.43 ± 0.6. Most students reported using social media, especially Facebook (mean 4.95 ± 1.7). The students reported a confidence level of information and communication technology (ICT) use of 3.4 ± 1.2. They also described their confidence in learning a new technology with a value of 3 ± 0.3. Almost 32.9% of the participants expressed an overall need for training on ICT tools. Conclusion: The overall preparedness of this group for ICT is moderate and needs improvement. This could be achieved through introducing changes in the taught curriculum.
Keywords: E-Health; health professional; information and communication technology; learning confidence